The effect of weed infestation towards rice growth of MR 219 rice variety / Umar Ahmad - Ahmad, Umar (Faculty of Plantation and Agrotechnology, 2019)
The topic of this study is ‘The effect of weed infestation toward rice growth of MR 219 rice variety’ are conducted to see how a 2 variety of weeds could affect the rice plants growth and production. The first objective are to study the effect of weed on the growth of rice. Based on the result, which kind of weeds could bring the most effect toward the rice yield production can be seen. While the second objective are to study the effect of weed on the yield of rice. This is to see which weed could affect the rice plant the most. The research are done using Completely Randomized Design design using 3 treatment, which consist of rice plant only as a control for treatment 1, rice plant with weedy Oryza sativa f. spontanea (weedy rice) as a treatment 2 and rice plant with Ludwigia hyssopifolia (water primrose) as treatment 3. Based on the result of plant height, tiller, biomass and grain weight, the rice plant are mostly not affected or insignificantly affected by the presence of weed in each sample. But, the panicle result show that the significant different in each treatment. This can support the hypothesis that there will be a different result between each treatments. In conclusion, it can be seen that Ludwigia hyssopifolia cause more harm than Oryza sativa f. spontanea to rice plant.